Bio-remediation and health management of salt affected soils - Arora, Sanjay (Indian Farming, 2020)
In view of the fact that both physical and chemical methods for reclamation of saline and sodic soils are not cost-effective and the halophilic plant growth promoting microbes have potential to ameliorate these soils. The halophilic bacterial strains can help in recovery of salt affected soils by directly supporting the growth of vegetation thus indirectly increasing crop yields in salt affected soils. Halophilic plant growth promoting bacteria have high potential for remediation of salt affected soils and enhancing productivity of crops especially paddy and wheat. The use of liquid bioformulations of halophilic plant growth promoters have not only helped in enhancing crop yields under salt stress but also have role in maintaining soil health.